Implementasi Kebijakan Pemungutan Pajak dan Retribusi Daerah Berbasis Daring - Said, Achmad Lamo; Hariyadi, Slamet; Agusman, Yudi (CV. Social Politic Genius (SIGn), 2024)
This research aims to analyze the implementation of an online-based policy for local tax and retribution collection by the Regional Revenue Agency in Kolaka Regency. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that implementing an online-based policy for local tax and retribution collection by the Regional Revenue Agency has made significant progress in several vital variables. The communication variable has been successful and effective, facilitating the acceptance of new technology and enhancing compliance with local taxes. However, the resource variable remains a significant constraint, with the inadequate allocation of human resources and facilities. The disposition variable shows exemplary commitment, but obstacles still exist in achieving tax collection targets and implementing all types of local tax and retribution. Meanwhile, the bureaucratic structure variable has functioned well, demonstrating effective coordination and collaboration that have strengthened the tax collection process and enhanced transparency and accountability in managing local taxes. Therefore, it is recommended that the Regional Revenue Agency enhance coordination with local government to advocate for a more significant allocation in the Regional Budget Revenue and Expenditure. The Regency House of Representatives and the Regent of Kolaka Regency should prioritize the procurement of technological infrastructure in the discussion of the Regional Budget Revenue and Expenditure, ensuring that the resource shortages faced by the Regional Revenue Agency can be overcome. For business operators, it is crucial to comply with tax recording devices during transactions to support local government policies in enhancing the transparency and accuracy of tax data. These improvements will not only support the smooth operation of the Regional Revenue Agency but also contribute to increased Regional Revenue that can be used for further development in Kolaka Regency.